how to solve this !
1. log(x^2+17)base3 = 4
2. log base2 (log 3 base9) = log 6 base x
3. log x base7 = 2log 6 base7 - log 4 base 7
4. log 6 base2 + log x base 2 = log 3 base 2 + log 10 base 2
1. log(x^2+17)base3 = 4
2. log base2 (log 3 base9) = log 6 base x
3. log x base7 = 2log 6 base7 - log 4 base 7
4. log 6 base2 + log x base 2 = log 3 base 2 + log 10 base 2
-
1.
x^2 + 17 = 3^4
x^2 + 17 = 81
x^2 = 81 - 17
x^2 = 64
x = +/- sqrt(64)
x = +/- 8
2.
2^(log 6 base x) = log 3 base 9
2^(log 6 base x) = 0.5
log 6 base x = log (base 2) of 0.5
log 6 base x = -1
x^(-1) = 6
x = 1/6
3.
log(x) = 2*log(6) - log(4)
log(x) = log(6^2) - log(4)
log(x) = log(36) - log(4)
log(x) = log(36/4)
log(x) = log(9)
x = 9
4.
log(6) + log(x) = log(3) + log(10)
6x = 3*10
6x = 30
x = 30/6
x = 5
x^2 + 17 = 3^4
x^2 + 17 = 81
x^2 = 81 - 17
x^2 = 64
x = +/- sqrt(64)
x = +/- 8
2.
2^(log 6 base x) = log 3 base 9
2^(log 6 base x) = 0.5
log 6 base x = log (base 2) of 0.5
log 6 base x = -1
x^(-1) = 6
x = 1/6
3.
log(x) = 2*log(6) - log(4)
log(x) = log(6^2) - log(4)
log(x) = log(36) - log(4)
log(x) = log(36/4)
log(x) = log(9)
x = 9
4.
log(6) + log(x) = log(3) + log(10)
6x = 3*10
6x = 30
x = 30/6
x = 5